Nanotoxicology and nanomedicine: The Yin and Yang of nano-bio interactions for the new decade - Bondarenko, Olesja; Mortimer, Monika; Kahru, Anne; Feliu, Neus; Javed, Ibrahim; Kakinen, Aleksandr; Lin, Sijie; Xia, Tian; Song, Yang; Davis, Thomas P.; Lynch, Iseult; Parak, Wolfgang J.; et al. (Nano today, 2021)
•Nanotoxicology and nanomedicine are two pillars of nanotechnology, representing the Yin and Yang of nano-bio interactions.•The applicability of nanotoxicology and the efficacy of nanomedicines may be improved by their knowledge transfer.•Routes of knowledge transfer between the two sub-disciplines are outlined and recommended in this Review.•A synergistic partnership between the two fields may benefit human and environmental health in the coming decade. Nanotoxicology and Nanomedicine are two sub-disciplines of nanotechnology concerning the adverse effects and health application of nanomaterials, respectively. This Perspective draws parallels and contrast between the two fields and calls for their close collaboration to address emerging challenges in global health. [Display omitted] Nanotoxicology and nanomedicine are two sub-disciplines of nanotechnology focusing on the phenomena, mechanisms, and engineering at the nano-bio interface. For the better part of the past three decades, these two disciplines have been largely developing independently of each other. Yet recent breakthroughs in microbiome research and the current COVID-19 pandemic demonstrate that holistic approaches are crucial for solving grand challenges in global health. Here we show the Yin and Yang relationship between the two fields by highlighting their shared goals of making safer nanomaterials, improved cellular and organism models, as well as advanced methodologies. We focus on the transferable knowledge between the two fields as nanotoxicological research is moving from pristine to functional nanomaterials, while inorganic nanomaterials – the main subjects of nanotoxicology – have become an emerging source for the development of nanomedicines. We call for a close partnership between the two fields in the new decade, to harness the full potential of nanotechnology for benefiting human health and environmental safety.